Photodynamic Therapy of Cancers With Internal Light Sources: Chemiluminescence, Bioluminescence, and Cerenkov Radiation - Zhang, Yintang; Hao, Yuanqiang; Chen, Shu; Xu, Maotian (Frontiers in Chemistry, 2020)
Photodynamic therapy is a promising and minimally invasive modality for the treatment of cancers. The use of self-illuminating system as light source provides an intriguing solution to the light-penetration issues of conventional PDT, which have gained considerable research interest in the past few years. This minireview aims to present an overview of self-illuminating PDT systems by using internal light sources (chemiluminescence, bioluminescence, and Cerenkov radiation) and give a brief discussion on the current challenges and future perspectives.